Kenya : Third Reviews Under the Extended Arrangement Under the Extended Fund Facility and Under the Arrangement Under the Extended Credit Facility, and Requests for Modification of Quantitative Performance Criteria, and Waiver of Applicability for Performance Criteria-Press Release; Staff Report; Staff Statement; and Statements by the Executive Director and by Staff Representative for Kenya. (IMF Staff Country Reports; Country Report, 2022)
Kenya's economy has been rebounding strongly in a challenging environment. Global shocks from the war in Ukraine and related trade disruptions-alongside more challenging financing conditions for frontier markets due to a normalization of monetary policy in advanced economies-will impact the external position in the near term. Inflation is set to increase, albeit temporarily, with the pass-through of global price shocks. Domestically, shortfall in rains and the continuing drought in the semi-arid regions are adding to uncertainties and pressuring vulnerable groups. The authorities view their IMF-supported program as a key policy anchor in the face of these shocks. While surging global fuel prices have made containing the cost of recently granted fuel subsidies urgent, Kenya's strong fiscal performance provides scope to cushion the adjustment to these shocks without exceeding program deficit targets. Strong performance of tax revenues is a key driver of this resilience. Policy tradeoffs will remain difficult, however, heading into August elections.